INVERSI IMPEDANSI ELASTIK UNTUK ESTIMASI KANDUNGAN RESERVOIR BATUPASIR LAPANGAN “Ve” FORMASI CIBULAKAN CEKUNGAN JAWA BARAT UTARA - Veratania Aisyah; Udi Harmoko (Youngster Physics Journal, 2012)
An Elastic Impedance inversion has been done for determine sandstone reservoir characterization of “Ve” Field Cibulakan Formation Northwest Java Basin. Amplitude Variation with Offset (AVO) inversion is done for determining Elastic Impedance reflectivity, near angle stack, mid angle stack, and far angle stack. Moreover Elastic Impedance inversion is done for determining Elastic Impedance volume. With DST 5 horizon for obtaining structure and slicing map to determine separating lithology of sandstone reservoir. In this research used seismic data and well data which only have a well. The step of data processing by analizing well data in order to get sensitive angle in separating lithology of sandstone and shale. Mudrock Line equation is used for this research because the available of log Vs can not reach the research target zone. Well seismic tie is done for obtaining horizon that approach the real geological zone. Initial model is made by used a control well and DST 5 horizon. From three inversion has been done Bandlimited, Sparse Spike, and Model Based inversion, Sparse Spike inversion is inversion method which gives accurate result. From that result of inversion volume is used for making slicing map intent on knowing of sandstone lithology separated. Based on analysis of Elastic Impedance inversion that content estimation of sandstone reservoir be in layer which have impedance 1348 (m/s)2gr/cc – 1365 (m/s)2gr/cc. Crossplot analysis result between log Elastic Impedance and log Gamma Ray shows that angle 350 is the best angle parameter in separating lithology of sandstone and shale. And from slicing map analysis on DST 5 horizon shows that zone distribution of sandstone reservoir have oriented north untill northeast.   Keyword: Elastic Impedance, AVO, inversion, Mudrock Line